1999
DOI: 10.1007/bfb0096509
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of stochastic approximation algorithms

Abstract: These notes were written for a D.E.A course given at Ecole Normale Supdrieure de Cachan during the 1996-97 and 1997-98 academic years and at University Toulouse III during the 1997-98 academic year. Their aim is to introduce the reader to the dynamical system aspects of the theory of stochastic approximations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
709
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 315 publications
(716 citation statements)
references
References 33 publications
5
709
0
2
Order By: Relevance
“…This is exactly what is done in Laslier et al (2001), Lemma 1, where, using terminology and results from Benaim (1999), it is shown that the replicator dynamics is an asymptotic-pseudo-trajectory of the learning process. Results of this type are useful in understanding the asymptotics of the reinforcement learning process, since they allow to show that Theorem 7.3 in Benaim (1999) applies and that the probability that the reinforcement learning process gets absorbed in an asymptotically stable Nash Equilibrium is strictly positive. However, to address general properties of convergence to Nash equilibria of reinforcement learning models, one needs to rule out convergence to all the other rest points of the replicator dynamics.…”
Section: An Overviewsupporting
confidence: 55%
See 4 more Smart Citations
“…This is exactly what is done in Laslier et al (2001), Lemma 1, where, using terminology and results from Benaim (1999), it is shown that the replicator dynamics is an asymptotic-pseudo-trajectory of the learning process. Results of this type are useful in understanding the asymptotics of the reinforcement learning process, since they allow to show that Theorem 7.3 in Benaim (1999) applies and that the probability that the reinforcement learning process gets absorbed in an asymptotically stable Nash Equilibrium is strictly positive. However, to address general properties of convergence to Nash equilibria of reinforcement learning models, one needs to rule out convergence to all the other rest points of the replicator dynamics.…”
Section: An Overviewsupporting
confidence: 55%
“…0 for t ! 1 4 In essence, the reason why this approximation result holds for random step sizes is related to that stated in Remark 4.3 of Benaim (1999) and therein references, namely that the approximation results of this type hold also for stochastic step sizes, when these are measurable with respect to =fx(n)g and square summable. This could o¤er an alternative way to prove Lemma 1.…”
Section: Notesmentioning
confidence: 76%
See 3 more Smart Citations